Experience of Architecture - Ar. Kabir Fatema, Dr. Jitendra Singh, Dr. Naresh Garg, Ar. Jayshree Deshpande (International Journal of Advanced Science and Technology, 2020)
Ever since Freudian space; Experience of Architecture has been a point of discussion. With Phenomenology and especially with Ponty; experiential analysis of Architecture began to be philosophically explored. With Neuroarchitecture there came a breakthrough in the analysis of Architectural experience. Simultaneously many theorists continued to explore the characters that played a role in the experience of architecture. These characters continue to be refined; this paper attempts at understanding the important characters that play a role in the experience of Architecture. Subject (User) and Object (Space) are the most important of characters. Space is further subdivided and explained in the paper. For an experience most vital is interaction between the Space and its User; which is called as Dialogue; Ideas of Dialogue leading to an experience are also elaborated here. The paper concludes with an inter-relationship diagram between the characters of Architectural experience that can lead into the Experiential Analysis of Architecture; which is the next stage of this research.